f(x) = -4x + 6
What needs to be done over here?
ok so what you would do is plug in these values into th ex and solve and find what y equals so lets do the first one togehther
f(1)=-4(1)+6 f(1)=2 (1,2)
Did u follow?
lol ok i will explain
we started off saying f(x)=-4x+6 so basically when it tells you f(1)=-4x+6 it means replace all x variables with 1 in this equation and then solve to find out what it would equal
ok so i will plug in 1 into the x variable so look: We want to find out what f equals ok? f=-4(1)+6 f=2 so when x equals 1 then f equals 2
So lets see what f will equal when x is 2 f(2)=-4(2)+6 What does f equal?
hellllooooo? are u there?
so what does f equal when x is 2? just do reg arithmetic
hey look i gave u the equation f(2)=-4(2)+6 Solve this for me
ok dont worry i am chilled
I just want u to solve the equation I gave you
Solve this for me f(2)=-4(2)+6
don't look at last time solve the equation do arithmetice f=-4(2)+6
ok I will help u solve this but this is basic arithmetic
ok so when x is 2 f is -2 ok so we write it like this (2,-2)
ok shld we put another value for x?
Like try solving for f when x is 3 ok?
Try it on ur own
ya y not?
ok so first write out the equation
yup that is the answer
So i guess u know what to do from now on!!!
It was great working with u :D BYE
what do u mean?
so either u can write it for example just 10 or f=10 or (-1,10)
Well these are the only 3 ways i know of
Idk what the computer wants LOL :D Computers are so complicating
Gonna go now
Join our real-time social learning platform and learn together with your friends!